The Influence of Occupational Safety and Health (K3), Individual Characteristics and Career Development on the Performance of Employees - Sulastri, Sulastri; Ahmad, Ahmad; Mappatompo, Andi (Journal of Public Representative and Society Provision, 2025)
This study aims to analyze the influence of Occupational Safety and Health (OHS), Individual Characteristics, and Career Development on Employee Performance at the Bulukumba Regency Fire Department. The background of this study is based on the importance of optimal human resource management, especially in high-risk work environments. The research approach used is quantitative with the causality method, where data were collected through questionnaires distributed to 183 respondents from a total population of 335 employees, using the Slovin formula in determining the sample. The results showed that OHS variables have a positive and significant effect on employee performance. The highest average value of OHS indicators was obtained for compliance with safety procedures, followed by the provision of PPE. This finding is reinforced by the results of interviews and field observations, which indicate that employees have a positive perception of OHS implementation, although there is still a need for improved health facilities and a comprehensive understanding of OHS. Other factors such as individual characteristics and career development were also found to contribute to improving employee performance. This study emphasizes the importance of implementing an effective OHS system, clear career development, and increasing individual capacity in creating a productive, safe, and sustainable work environment.